2017
DOI: 10.1038/s41598-017-14463-0
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Doped Heterojunctions in TiO2 Nanotubes: An Efficient Photocatalyst for Solar Water Splitting

Abstract: The two important factors that affect sunlight assisted water splitting ability of TiO2 are its charge recombination and large band gap. We report the first demonstration of nitrogen doped triphase (anatase-rutile-brookite) TiO2 nanotubes as sun light active photocatalyst for water splitting with high quantum efficiency. Nitrogen doped triphase TiO2 nanotubes, corresponding to different nitrogen concentrations, are synthesized electrochemically. Increase in nitrogen concentration in triphase TiO2 nanotubes is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 73 publications
4
49
0
Order By: Relevance
“…On the basis of the existing literature, the shift effect is indicative of lattice disorder defects. It can be caused by oxygen vacancies, 29,30 the electronic interaction between titania and nitrogen doping, 27,31 or the change in particle size. 32,33 SEM is also employed to characterize the microstructure of the films and to provide more evidence about the shift in Raman spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the basis of the existing literature, the shift effect is indicative of lattice disorder defects. It can be caused by oxygen vacancies, 29,30 the electronic interaction between titania and nitrogen doping, 27,31 or the change in particle size. 32,33 SEM is also employed to characterize the microstructure of the films and to provide more evidence about the shift in Raman spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The proposed formulas are shown in Eq. 1a – c below [ 16 , 35 , 36 ]. where W A , W B , and W R represent the weight fractions of anatase, brookite, and rutile.…”
Section: Resultsmentioning
confidence: 99%
“…92 Moreover, band gap engineering via doping, decoration and/or alloying with different elements (metals or non-metals) was reported to extend its light harvesting into the visible region of the solar spectrum. 93,94 David et al 95 reported the impact of loading TNTs, fabricated via rapid breakdown anodization, with Pt, Pd and Ni nanoparticles on the efficiency of hydrogen generation via solar water splitting. The as-prepared TNTs were annealed at 450 C for 3 h then sensitized with the metal nanoparticles through the chemical reduction approach using NaBH 4 .…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2019 Nanoscale Adv., 2019, 1, 2801-2816 | 2807 Creative Commons Attribution 3.0 Unported Licence.from brookite to anatase. The photocatalytic measurements revealed that doping TiO 2 with a nitrogen concentration of 0.29 atomic percentage exhibited the best photocatalytic performance in hydrogen production (30.2 mmol g À1 ) via solar water splitting 94. …”
mentioning
confidence: 99%